Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan PT Askrindo Jakarta Timur - Agnes Tio Natasya Hutabarat; Siwi Nur Indriyani (Jurnal Ekonomi dan Industri, 2025)
The purpose to determine the effect of work motivation and work discipline on employee performance PT Askrindo East Jakarta. This research is included in the category of causal associative research using a quantitative approach. The research population amounted to 50 people, the sampling technique used a saturated sample, all members of the population were used as samples totaling 50 employees of PT Askrindo East Jakarta. The research method uses simultaneous and partially linear regression analysis. The results of the study indicate that in simultaneous or partially ways, work motivation and work discipline have a positive and significant effect on the performance of employees of PT Askrindo East Jakarta.